PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR ADVERTISING, PRINTING, DAN MEDIA YANG TERDAFTAR DI BEI TAHUN 2008-2013 - Umi Rahmawati; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of Intellectual Capital on Financial Performance. Independent variable used ini this study VACA, VAHU, SCVA, and VAIC. Dependent variable used in this study is financial performance such as ROA and MB The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2008 - 2013. Sampling method used is purposive sampling. A criterion for advertising, printing, and media. Another criteria is the firm must listing, experienced profit, and complete data. Total data of this study is 54 data. Then, there are 11 samples that include outlier should be excluded from samples of observation. So, the final amounts of the sample are 43 data. Multiple regression used to be analysis technique.The empirical result of this study show that Intellectual Capital expertise on has positively significant  influenced  ROA  &  MB. Human  Capital  expertise  on  has  positively  significant influenced ROA & MB. Human Capital relatively plays a more significant role when compared to Physical Capital and Structural Capital to ROA & MB.